New Deal Modernism : American Literature and the Invention of the Welfare State - Szalay, Michael, 1967- (Book collections on Project MUSE., 2000)
In New Deal Modernism Michael Szalay examines the effect that the rise of the welfare state had on American modernism during the 1930s and 1940s, and, conversely, what difference this revised modernism made to the New Deal's famed invention of "Big Government."Szalay situates his study within a liberal culture bent on security, a culture galvanized by its imagined need for private and public insurance. Taking up prominent exponents of social and economic security-such as Franklin Delano Roosevelt, John Maynard Keynes, and John Dewey-Szalay demonstrates how the New Deal's rev.